(untitled) (Research, Society and Development, 2024)
Introduction: Endocrine contaminants (EC) affect the endocrine system of several living organisms. Among the substances classified as CE, bisphenol-A (BPA) and 17β-estradiol (E2) stand out. These compounds may be present in the water supply of many cities and urban centers. Objective: To identify the presence of endocrine contaminants in the water supply of the city of Itu, State of São Paulo (SP), using Artemia salina as a bioindicator. Methodology: Tests for EC detection were carried out in water supply from the city of Itu/SP, analysis of physicochemical characteristics and cytotoxicity tests with A. salina. Results: Cytotoxicity was found in the waters evaluated from 10%, indicating a highly toxic substance. No estradiol and bisphenol-A were detected in the samples during the summer and winter seasons of 2021. Conclusion: The importance of the existence of parameters for water quality for EC in current Brazilian legislation is highlighted, regarding water quality, In other words, it is necessary to reevaluate and establish new potability standards for consumption, taking into account that these substances (EC) are harmful to health even in very small concentrations.